Supporting survivors of sexual violence: protocol for a mixed-methods, co-research study of the role, funding and commissioning of specialist services provided by the voluntary sector in England. Issue 12 (17th December 2019) - Combes, Gill; Damery, Sarah; Gunby, Clare; Harlock, Jenny; Isham, Louise; Jones, Alice; Maxted, Fay; Parmar, Priti; Schaub, Jason; Smith, Deb; Taylor, Julie; Bradbury-Jones, Caroline
Abstract : Introduction: The voluntary sector provides a range of specialist services to survivors of sexual violence, many of which have evolved from grass roots organisations responding to unmet local needs. However, the evidence base is poor in terms of what services are provided to which groups of survivors, how voluntary sector specialist (VSS) services are organised and delivered and how they are commissioned. This will be the first national study on the role of the voluntary sector in supporting survivors in England. Methods and analysis: This study uses an explanatory sequential naturalistic mixed-methods design with two stages. For stage 1, two national surveys of providers' and commissioners' views on designing and delivering VSS services will facilitate detailed mapping of service provision and commissioning in order to create a taxonomy of VSS services. Variations in the national picture will then be explored in stage 2 through four in-depth, qualitative case studies using the critical incident technique to explain the observed variations and understand the key contextual factors which influence service provision. Drawing on theory about the distinctive service contribution of the voluntary sector, survivors will be involved as co-researchers and will play a central role in data collection and interpretation. Ethics and dissemination: Ethical approval has been granted by the University of Birmingham research ethics committee for stage 1 of the project. In line with the sequential and co-produced study design, further applications for ethical review will be made in due course. Dissemination activities will include case study and end-of-project workshops; good practice guides; a policy briefing; project report; bitesize findings; webinars; academic articles and conference presentations. The project will generate evidence about what survivors want from and value about services and new understanding about how VSS services should be commissioned and provided to support survivors to thrive in the long term.